Menciptakan Pesantren Berkemajuan Sebagai Bagian dari Ekosistem Pintar Era Society 5.0 - Satria Kamal Akhmad (Jurnal Studi Pesantren, 2025)
Society 5.0 demands that pesantren adapt to technological developments without neglecting Islamic values. This research aims to identify the relevance of the society 5.0 concept to pesantren education and the strategies that can be applied to become part of the smart ecosystem. Through the Systematic Literature Review (SLR) approach, this research found that several pesantren have adopted digital technology in their curriculum, such as e-learning and digital literacy. However, challenges such as limited technological infrastructure and human resources have become the main obstacles. This research concludes that pesantren have great potential to remain relevant and contribute in the digital era, as long as they are willing to continue innovating and collaborating with various parties.